2004
DOI: 10.1007/s00167-003-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

Drop foot after high tibial osteotomy: a prospective study of aetiological factors

Abstract: Drop foot is not uncommon after high tibial osteotomy for genu varum. The authors report their results of a prospective study of 16 patients operated on between May 1990 and May 1991. All patients had medial femoro-tibial osteoarthritis with a constitutional genu varum. They all had a subtraction valgus high tibial osteotomy fixed by a blade plate. The experimental protocol included clinical review, antero-lateral compartment pressure measurements, intra- and post-operative electromyography, assessment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Numerous case reports describe foot-drop in association with unusual aetiology, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the outcomes of operative management or rehabilitation for this disabling deficit have been described. [19][20][21][22] Some publications describe the natural history and patterns of neural compression in patients with ADF weakness due to lumbar compressive pathology and only a few articles specifically evaluate the recovery of ADF weakness after decompressive surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous case reports describe foot-drop in association with unusual aetiology, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the outcomes of operative management or rehabilitation for this disabling deficit have been described. [19][20][21][22] Some publications describe the natural history and patterns of neural compression in patients with ADF weakness due to lumbar compressive pathology and only a few articles specifically evaluate the recovery of ADF weakness after decompressive surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-existing neuropathies have been identified as risk factors in nerve palsies. 4. Was the femur alone operated?…”
Section: Bilateral Foot Drop: Looking For the Needle In The Wrong Haymentioning
confidence: 99%
“…If they were also operated upon, the foot drop could be related to the surgery. 4 5. What was the position of the patient during surgery?…”
Section: Bilateral Foot Drop: Looking For the Needle In The Wrong Haymentioning
confidence: 99%
“…Gibson et al [12] and Bauer et al [13], however, have shown that there is an increase in compartment pressures with this technique, leading to the possibility of an anterior compartment syndrome. Gibson et al [12] showed that there was significant elevation of the anterior compartment pressures to greater than 45 mmHg in the majority of the study group (7 out of 10) where the compartment was not drained, with five of them experiencing transient clinical signs.…”
Section: Compartment Syndromementioning
confidence: 99%
“…The proximity of the nerve to the fibular head and neck is thought to be a causative factor as well as several other anatomical and surgical factors. Bauer et al [13] identified two direct factors that contributed to this complication, namely, direct trauma to the nerve secondary to a high fibular osteotomy and high compartment pressure due to poor haemostasis or inadequate drainage. They also identified two related factors: use of a tourniquet, which sensitises the nerve, and stretching of the nerve during correction of the deformity.…”
Section: Neurovascular Complicationsmentioning
confidence: 99%